Ambidextrous leadership, paradox and contingency: evidence from Angola - Cunha, M. P. E. (2018)
The study departs from two assumptions. First, it considers that organizations, their leaders and the HRM function are inherently paradoxical and that, in that sense, dealing with paradox is a necessary component of the leadership process which requires ambidexterity capabilities. Second, it explores whether the paradoxes of leadership may manifest differently in different contexts. We explore the emergence of paradox in the leadership of Angolan organizations. Angola is an economy transitioning from a centrally planned to a market mode, and this makes it a rich site for understanding the specificities of ambidextrous paradoxical processes in an under-researched, ‘rest of the world’, context. The findings of our inductive study led to the emergence of four interrelated paradoxes and highlight the importance of ambidextrous paradoxical work as a HRM contingency.